Attaching Photochemically Active Ruthenium Polypyridyl Complex Units to Amorphous Hydrogenated Carbon (a‐C:H) Layers. Issue 2 (27th December 2018) - Schink, Carina; Catena, Alberto; Heintz, Katharina; Görls, Helmar; Beresko, Christian; Ankerhold, Georg; von der Au, Marcus; Meermann, Björn; Van Malderen, Stijn J. M.; Vanhaecke, Frank; Wehner, Stefan; Imhof, Wolfgang; et al.
Abstract: Amorphous hydrogenated carbon (a‐C:H) films are applied 500 nm thick on Si(100) via plasma‐enhanced chemical vapor deposition (PECVD) using ethyne. Present plasma conditions enrich the sp 2 ‐content especially toward the outermost a‐C:H layers, which in turn are used to attach a photoactive Ru‐polypyridyl complex to the surface. An azo‐bridged dinuclear Ru‐polypyridyl complex is optimized in synthesis and the final mononuclear fragment attached on a‐C:H photochemically under UV‐irradiation with concomitant N2 release. The Ru‐polypyridyl complex is characterized by MS, NMR, IR, UV/vis, fluorescence spectroscopy, and time‐dependent density functional theory (DFT) calculations. Crystallographic data for the intermediate 4‐nitro‐2‐(pyridin‐2‐yl)pyridine 1‐oxide as essential precursor are established. Morphological characteristics of the a‐C:H @ Si and final Ru(complex) @ a‐C:H @ Si combinations are determined by atomic force microscopy (AFM) revealing individual grain‐like structures. The presence of Ru on the a‐C:H @ Si surface is initially verified qualitatively by laser‐induced breakdown spectroscopy (LIBS) and by inductively coupled plasma‐sector field mass spectrometry (ICP‐SF‐MS) after chemical digestion. With laser ablation‐ICP‐MS mapping, full Ru coverage is proven, also revealing inhomogeneities in terms of "Ru hot spots". The current investigation proves the successful attachment of a Ru‐complex on a‐C:H and indicates a starting point for the development of further material combinations for feasible sunlight to energy conversions. Abstract : Via surface functionalization a photoactive Ru‐polypyridyl complex is attached on a thin a‐C:H film by UV irradiation from an azo‐bridged dinuclear Ru‐polypyridyl precursor. The carbon film previously deposited on Si(100) is sp 2 ‐enriched by current plasma conditions allowing the attachment. Laser ablation‐inductively coupled plasma‐mass spectrometry mapping demonstrates full Ru coverage with additional Ru hot spots distributed irregularly.